A contribution to the knowledge of the genus Lacvietina Herman (Coleoptera: Staphylinidae: Tachyporinae) from China - Chang, Yuan; Li, Li-Zhen; Yin, Zi-Wei (Zootaxa, 2019)
The tachyporine genus Lacvietina Herman is represented in China by two species: L. punctatissima (Hayashi) from Taiwan and L. lii (Li, Tang & Zhu) from Guizhou. Here we described a third species, L. nabanhensis Chang, Li & Yin, sp. nov., from Yunnan. Moreover, new collecting data and a redescription of L. lii are provided.